EVALUATION OF THE IMPLEMENTATION OF THE TAHFIZH SPT PROGRAM AT SMPN ACEH BESAR REGENCY: A REVIEW FROM THE PERSPECTIVE OF PLANNING AND IMPLEMENTATION - Ramadhani, Shaufi; Marzuki, Marzuki (Jurnal As-Salam, 2025)
This study aims to evaluate educators' and students' planning in the Integrated Education System (SPT) program in the field of tahfizh at the junior high school (SMP) level in Aceh Besar Regency. The evaluation used a quantitative approach involving 12 educators and 361 students. Data collection was carried out using a questionnaire that had undergone content validation (Aiken's) and reliability (Cronbach's Alpha). The educators' evaluation results at the planning stage averaged 4.44, with a "Very Good" rating, and the students' evaluation results averaged 3.81, with a "Good" rating. Based on the results of this planning evaluation, the recommendations that can be given are that educators can use a variety of methods in tahfizh learning, need to conduct initial diagnostic tests to determine the learning styles and methods that are suitable for students, evaluate student responses to the learning methods used, and collaborate in the preparation of teaching modules that integrate several learning methods in accordance with the characteristics of the students. These findings emphasize the importance of adjusting learning strategies and improving planning quality to better align with student needs, enabling the objectives of the tahfizh program to be achieved optimally.